Determining the H i content of galaxies via intensity mapping cross-correlations. Issue 3 (9th June 2017) - Wolz, L.; Blake, C.; Wyithe, J. S. B.
Abstract: We propose an innovative method for measuring the neutral hydrogen (H i ) content of an optically selected spectroscopic sample of galaxies through cross-correlation with H i intensity mapping measurements. We show that the H i -galaxy cross-power spectrum contains an additive shot noise term that scales with the average H i brightness temperature of the optically selected galaxies, allowing constraints to be placed on the average H i mass per galaxy. This approach can estimate the H i content of populations too faint to directly observe through their 21-cm emission over a wide range of redshifts. This cross-correlation, as a function of optical luminosity or colour, can be used to derive H i -scaling relations. We demonstrate that this signal will be detectable by cross-correlating upcoming Australian Square Kilometre Array Pathfinder observations with existing optically selected samples. We also use semi-analytic simulations to verify that the H i mass can be successfully recovered by our technique in the range M_H I > 10^8 M_, in a manner independent of the underlying power spectrum shape. We conclude that this method is a powerful tool to study galaxy evolution, which only requires a single intensity mapping data set to infer complementary H i gas information from existing optical and infrared observations.